Scorch - Damico, Gina. (Boston : Houghton Mifflin Harcourt, 2012)
Sixteen-year-old grim reaper Lex Bartleby tries to redeem herself among her fellow Grims by finding renegade Zara, who is indiscriminately damning souls, and stopping her once and for all.
Keywords: Death -- Fiction; Future life -- Fiction; Humorous stories; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Family / General (see also headings under Social Issues).; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Horror & Ghost Stories; JUVENILE FICTION / Law & Crime; JUVENILE FICTION / Social Issues / Death & Dying; JUVENILE FICTION / Visionary & Metaphysical; JUVENILE FICTION / Mysteries & Detective Stories